2003
DOI: 10.1055/s-2003-38983
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intracoronary Administration of Vitamin E on Myocardial Ischemia-Reperfusion Injury During Coronary Artery Surgery

Abstract: Administration of vitamin E into the coronary arteries before removal of the aortic cross-clamp can reduce myocardial cell injury and protect the myocardium from ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
0
18
1
1
Order By: Relevance
“…Canbaz et al demonstrated the beneficial effect of intracoronary administration of vitamin E (100 mg) at the end of aortic cross clamping during coronary artery surgery on myocardial cell injury. The endpoint in this study was troponine-I release and lactate production [62]. In contrast, Lassnigg et al [63] demonstrated no effect of intravenously administration of vitamin E (4 times 270 mg, between 12 h before until 2 days after cardiac surgery).…”
Section: Odrf-scavengers/antioxidantiacontrasting
confidence: 58%
“…Canbaz et al demonstrated the beneficial effect of intracoronary administration of vitamin E (100 mg) at the end of aortic cross clamping during coronary artery surgery on myocardial cell injury. The endpoint in this study was troponine-I release and lactate production [62]. In contrast, Lassnigg et al [63] demonstrated no effect of intravenously administration of vitamin E (4 times 270 mg, between 12 h before until 2 days after cardiac surgery).…”
Section: Odrf-scavengers/antioxidantiacontrasting
confidence: 58%
“…However, these protective effects decreased as the time passed. It is not clear wheather this effect might be related to the preoperative dosage given, because there is no report on a standardized scheme of dose for the parenteral use of vitamin E. 21 The TAC levels in the vitamin E group were higher than in the control group in the early phase of the operation, which implied that vitamin E had a major role in the serum TAC level. Although the levels of TAC and MDA were similar at 60 minutes, electron-microscopic examination revealed that there were more patients with grade 2 injury than those with grade 3 injury at 60 minutes in the vitamin E group, whereas in the control group, there were more patients with grade 3 injury.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of cardioprotection was obtained in the context of cardiac surgery: in patients undergoing CABG, treatment with α-tocopherol improved the recovery of systolic and diastolic function [313]. Likewise, intracoronary administration of vitamin E (100 mg) at the end of aortic cross clamping reduced troponin-I release and lactate production [314]. However, a randomized trial failed to demonstrate a beneficial effect of intravenous superoxide dismutase on global or regional left ventricular function in patients who underwent PTCA for the treatment of acute myocardial infarction [315] and a recent large trial has shown that 600 IU of natural source vitamin E did not provide overall benefit for major cardiovascular events or affect total mortality [316].…”
Section: Interventions Which Interfere With the Mechanisms Of Ischemimentioning
confidence: 99%